The causes and consequences of inflation in Ukraine - Проданова, І. І.; Мацьків, Р. Т. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
In the article the authors explored the interrelated macroeconomic impact on inflation processes in the country, considered the causes and social and economic consequences. The problems of inflation in Ukraine, outlined the activities and effectiveness of anti-inflation regulation were analyzed by the authors.